2013
DOI: 10.1371/journal.pone.0080578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Oral Subchronic Exposure of Deoxynivalenol on the Composition of Human Gut Microbiota in a Model of Human Microbiota-Associated Rats

Abstract: BackgroundDeoxynivalenol (DON), a mycotoxin produced by Fusarium species, is one of the most prevalent mycotoxins present in cereal crops worldwide. Due to its toxic properties, high stability and prevalence, the presence of DON in the food chain represents a health risk for both humans and animals. The gastrointestinal microbiota represents potentially the first target for these food contaminants. Thus, the effects of mycotoxins on the human gut microbiota is clearly an issue that needs to be addressed in fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 59 publications
(46 reference statements)
2
33
1
Order By: Relevance
“…For all samples collected from pigs in rooms 1A to 1D, previously validated quantitative PCR (qPCR) analyses, all targeting 16S rRNA gene fragments, were carried out to evaluate the change in abundance of the total bacterial population and of the numbers of Bacteroides/Prevotella, Bifidobacterium, E. coli, Enterococcus, and Lactobacillus/ Leuconostoc/Pediococcus (23). qPCR for quantification of bla CTX-M-1 gene copies was performed (24) for samples collected from the six animal rooms during the first week and from rooms 1A to 1D thereafter; the copy numbers were determined by comparison with decimal dilutions of plasmid DNA prepared from the bla CTX-M-1 gene previously cloned in the plasmid pCR4-TOPO in the One Shot TOP10 E. coli strain (Life Technologies, St. Aubin, France), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For all samples collected from pigs in rooms 1A to 1D, previously validated quantitative PCR (qPCR) analyses, all targeting 16S rRNA gene fragments, were carried out to evaluate the change in abundance of the total bacterial population and of the numbers of Bacteroides/Prevotella, Bifidobacterium, E. coli, Enterococcus, and Lactobacillus/ Leuconostoc/Pediococcus (23). qPCR for quantification of bla CTX-M-1 gene copies was performed (24) for samples collected from the six animal rooms during the first week and from rooms 1A to 1D thereafter; the copy numbers were determined by comparison with decimal dilutions of plasmid DNA prepared from the bla CTX-M-1 gene previously cloned in the plasmid pCR4-TOPO in the One Shot TOP10 E. coli strain (Life Technologies, St. Aubin, France), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…DON exposure is also related to acute gastrointestinal disorder and inhibition of DNA and protein synthesis, which leads to immune‐suppression (Sun, Su, & Shan, ). The ingestion of DON also poses a great threat to human health through serious modulations in the composition of the human gut microflora, which affects normal host functions (Saint‐Cyr, Perrin‐Guyomard, Houee, Rolland, & Laurentie, ). DON derivatives (DON‐3‐glucoside, 15‐acetyldeoxynivalenol, and 3‐acetyldeoxynivalenol) are equally a safety concern for consumers (Vidal, Mengelers, Yang, De Saeger, & De Boevre, ).…”
Section: Protection Provided By Lab Against the Toxic Effects Of Mycomentioning
confidence: 99%
“…Although there are indications that DON exposure might disrupt the balance and diversity of commensal microbiota and cause dysbiosis, as reported in one pig study (Waché et al, 2009), the information regarding the potential impacts of DON on gut microbiota in pigs and chickens is still scarce. One recent study, conducted in a rat model, evaluated the impact of a chronic exposure of DON on the composition of gut microbiota (Saint-Cyr et al, 2013). These authors reported that during oral DON exposure (100 μg kg -1 body weight for 4 weeks), a significant increase was observed in Bacteroides spp.…”
Section: Effects Of Don On Gut Commensal Microbiotamentioning
confidence: 99%
“…Therefore, this area of research needs to be addressed in domestic animals including poultry and pigs using molecular microbiological techniques that allow a deep evaluation of the communities, function, and their metabolic activity. Major attention should also be given to the elucidation of the effects of dose and duration of DON exposure because ingestion of DON for long periods and at different doses may have adverse effects on the intestinal microbiota and their metabolic activity (Saint-Cyr et al, 2013). Also, because diet has an important impact on the diversity of gut microbiota of pigs (Metzler-Zebeli et al, 2009Mann et al, 2014) and poultry (Stanley et al, 2013), further research is needed to evaluate interactions among dietary ingredients or additives (probiotics, prebiotics and phytobiotics) and DON exposure on the gut microbiota of pigs and poultry.…”
Section: Effects Of Don On Gut Commensal Microbiotamentioning
confidence: 99%